suPAR is a Bad Omen for Chronic Kidney Disease Progression (Indian Journal of Forensic Medicine & Toxicology, 2020)
The rationale for considering serum soluble- urokinase plasminogen activator receptor (s-uPAR) concentration as a potential biomarker for incipient CKD was primarily based on reports that increased levels of this receptor will serve as a circulating permeability variable that may be impaired at the start of FSGS and DN, a crucial explanation for CKD. So in early stages(1-3) of CKD, suPAR was evaluated. The aims of present paper are to investigate whether patients with CKD have distinct circulating suPAR, that could lead to a potential development of noninvasive diagnostic biomarkers of the disease. And finally using healthy subjects as a control group to determine specificity and sensitivity . 135 subjects were incorporated in this study, 30 were healthy control, with mean age 48.7±9.7years, and they were 14 males and 16 females. 105CKD patient , with mean age 50.1±10.0years, they were 54 males and 51 females. Blood samples were collected. Serum after centrifugation was isolated for estimation of suPAR by Enzyme linked immune sorbent assay , creatinine, and urea by enzymatic method . Early morning urine sample was collected to be used for determination albumin creatinine ratio in patient . suPAR level was higher in CKD patients than in healthy control, 6.179±2.221 versus 2.303±0.475, respectively; the difference was highly significant (P < 0.001) .To study the potential role of suPAR in diagnosis of patients with CKD, ROC showed that the cutoff value of suPAR was > 3.5 ng / ml fold shift with sensitivity and specificity; the AUC was 0.826 (95 % confidence interval: 0.690-0.920) and therefore 82.6 % precision and significance level of (P < 0.001). In conclusion, The suPAR is significantly more effective and also more comprehensive to CKD clinical assessment and can be supported with creatinine blood analysis.